IMPACT OF OLIVE LEAVES SUPPLEMENTATION IN AWASSI RATION ON SOME PRODUCTIVE AND BIOCHEMICAL BLOOD TRAITS - Alaa Salh; Khalid ِSultan (Mesopotamia Journal of Agriculture)
The research was conducted to assess the effects of supplementing olive leaves on growth parameters and serum blood biochemical characteristics of Awassi lambs. Twenty-four (6 lambs/group and 5-6 month aged) with average weight (25.85±0.13 Kg) were assigned randomly into four groups. In the first group: T1, lambs were fed only standard ration (control). In the second, third and fourth groups, T2, T3 and T4, lambs were fed standard ration supplemented with olive leaves (25,50 and 75 gm/kg ration daily). The study lasted for twelve weeks. BW, BWG at two weeks, and RMG were detected. Serum blood (CHO, TRI, GLU, ALB, GLO and TP), were also estimated. The results illustrated BW increased significantly (P≤0.5) in T2 at the 4th and 6th weeks, while all olive leaf treatments supersized substantially at the 12th weeks of the study. Also, in T2, T3, and T4 lambs, body weight gain increased significantly at 10th compared with control, while T4 lambs had higher BWG considerably at the 12th week of the study. A significant effect was noticed in RMG in T1 lambs in the 12th week. The supplementing of olive leaves caused a substantial decrease in GHO of T4 and TRI of all treated lambs' blood serum in 1st month of the study. The same results were gained in 3rd month of the study. Also, TP increased significantly (P≤0.5) in T3 and T4 treatments in 3rd month of the study. In general, adding olive leaves to the diet of fattened lambs improves growth performance and some blood biochemical parameters.